Genetic predisposition to alcoholism, schizophrenia and Alzheimer’s disease with psychodiagnostic characteristics in russian population - A. V. Marusin; A. N. Kornetov; M. G. Swarovskaya; K. V. Vagaitseva; E. S. Pavlenyuk; V. A. Stepanov (Бюллетень сибирской медицины)
The purpose of this paper is to identify genetic factors connected with personal features using the panel of 12 polymorphic markers associated with the risk of developing dementia in patients with Alzheimer’s disease, schizophrenia and alcoholism.Materials and methods. The correlation among quantitative traits of personality, temperament and character determined with Cattell’s (the Sixteen personality factor questionnaire (16PF)), Leonhard-Schmieschek’s, Spielberger-Khanin’s, and Eysenck’s (IQ) tests were analyzed with polymorphic variants of 12 genes involved in the development of severe mental disorders such as alcoholism, schizophrenia and Alzheimer’s disease. DNA samples of 150 students were genotyped using PCR-RPLF method. The data were processed by nonparametric statistical methods.Results. Interallelic nonrandom associations in paired combinations of GABRA2-PICALM, PICALMADCY3, CLU-CBX7 and CLU-ADCY3 polymorphisms were detected. This may indicate the adaptive selection influencing the maintenance of behavioral homeostasis in population. A number of statistically significant associations of genetic variation were found: CLU with perfectionism(Q3) of 16PF and the exaltation of the Leonhard’s tests, PICALM with tension (Q4) of 16PF and the imbalance of Leonhard’s tests, DISC1 with vigilance(L) of 16PF, and exaltation, cyclothymia of Leonhard’s tests, ZNF804A with imbalance by Leonhard’s test, SLC6A4 with reasoning(B) of 16PF test, ADCY3 with self-reliance(Q2) and extraversion(F2) of 16PF test, MIR9-2 emotional stability(C), liveliness(F), social boldness(H), extraversion(F2) of 16PF, and dysthymia, hyperthymia of Leonhard’s tests, with the personal anxiety of Spielberger-Khanin’s test, CBX7 with vigilance(L), warmth(A) of 16PF test, SLC6A3 with IQ.Conclusion. These findings support the idea of overlapping genetic component in common mental and neurological disorders and variability of human cognitive and personality traits.